Systemic Immune Activation and HIV Shedding in the Female Genital Tract. (1st February 2016) - Spencer, LaShonda Y.; Christiansen, Shawna; Wang, Chia-Hao H.; Mack, Wendy J.; Young, Mary; Strickler, Howard D.; Anastos, Kathryn; Minkoff, Howard; Cohen, Mardge; Geenblatt, Ruth M.; Karim, Roksana; Operskalski, Eva; et al.
Abstract : Background: Plasma HIV RNA is the most significant determinant of cervical HIV shedding. However, shedding is also associated with sexually transmitted infections (STIs) and cervical inflammation. The mechanism by which this occurs is poorly understood. There is evidence that systemic immune activation promotes viral entry, replication, and HIV disease progression. We hypothesized that systemic immune activation would be associated with an increase in HIV genital shedding. Methods: Clinical assessments, HIV RNA in plasma and genital secretions, and markers of immune activation (CD38 + DR + and CD38 − DR − ) on CD4 + and CD8 + T cells in blood were evaluated in 226 HIV+ women enrolled in the Women's Interagency HIV Study. There were 569 genital evaluations of which 159 (28%) exhibited HIV RNA shedding, defined as HIV viral load >80 copies per milliliter. We tested associations between immune activation and shedding using generalized estimating equations with logit link function. Results: In the univariate model, higher levels of CD4 + and CD8 + T-cell activation in blood were significantly associated with genital tract shedding. However, in the multivariate model adjusting for plasma HIV RNA, STIs, and genital tract infections, only higher levels of resting CD8 + T cells (CD38 − DR − ) were significantly inversely associated with HIV shedding in the genital tract (odds ratios = 0.44, 95% confidence interval: 0.21 to 0.9, P = 0.02). Conclusions: The association of systemic immune activation with genital HIV shedding is multifactorial. Systemic T-cell activation is associated with genital tract shedding in univariate analysis but not when adjusting for plasma HIV RNA, STIs, and genital tract infections. In addition, women with high percentage of resting T cells are less likely to have HIV shedding compared with those with lower percentages. These findings suggest that a higher percentage of resting cells, as a result of maximal viral suppression with treatment, may decrease local genital activation, HIV shedding, and transmission.